Debating Special Education - Farrell, Michael (London Routeldge Taylor & Franics Group, 2010)
Examining a range of criticisms made of special education, this title analyses several key debates in special education giving critical responses to inform policy and practice for the future of special education. It identifies possible limitations to the special education knowledge base and provision.
Include Bibliography and Index
Keywords: Special education -- Educational psychology -- Effective teaching